Требования к построению негёделевских информационных систем - Евланов, М. В.; Неумывакина, О. Е. (ХНУРЭ, 2008)
Problems of information systems working out theoretical basis improvement are considered. Basic requirements to information system construction are formulated. These requirements will direct to overcoming of negative influence of practical consequences from Geodel theorem about incompleteness. Formulated requirements allow to determine principles of theoretical task on non-Geodel intellectual information system working out.
Keywords: построение информационных систем